Benson's microbiological applications : laboratory manual in general microbiology - Brown, Alfred E. (New York : McGraw Hill Education, 2012)
A laboratory manual that covers microbiological applications. It includes 77 self-contained, and illustrated exercises. It is suitable for either a majors or non-majors lab course.
Part 1 Microscopy -- Part 2 Survey of Microorganisms -- Part 3 Manipulation of Microorganisms -- Part 4 Staining and Observations of Microorganisms -- Part 5 Culture Methods -- Part 6 Bacterial Viruses -- Part 7 Environmental Influences and Control of Microbial Growth -- Part 8 Identification of Unknown Bacteria -- Part 9 Miniaturized Multitest Systems -- Part 10 Diversity and Environmental Microbiology -- Part 11 Applied Microbiology -- Part 12 Bacterial Genetics and Biotechnology -- Part 13 Medical Microbiology -- Part 14 Immunology and Serology.
Includes bibliographical references and index.
Keywords: LABORATORY MANUALS